Mechanisms and pathways of Toxoplasma gondii transepithelial migration. Issue 1 (2nd January 2017) - Jones, Emily J.; Korcsmaros, Tamas; Carding, Simon R.
ABSTRACT: Toxoplasma gondii is a ubiquitous parasite and a prevalent food-borne parasitic pathogen. Infection of the host occurs principally through oral consumption of contaminated food and water with the gastrointestinal tract being the primary route for entry into the host. To promote infection, T. gondii has evolved highly specialized strategies for rapid traversal of the single cell thick intestinal epithelial barrier. Parasite transmigration via the paracellular pathway between adjacent cells enables parasite dissemination to secondary sites of infection where chronic infection of muscle and brain tissue is established. It has recently been proposed that parasite interactions with the integral tight junction (TJ) protein occludin influences parasite transmigration of the intestinal epithelium. We review here the emerging mechanisms of T. gondii transmigration of the small intestinal epithelium alongside the developing role played in modulating the wider TJ-associated proteome to rewire host cell regulatory systems for the benefit of the parasite.